Drivers and barriers to effective construction project monitoring and evaluation at the metropolitan, municipal and district assemblies (mmdas) in the greater Accra region - Lawson, Anthony (2021)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the Award Degree of Master of Science in Construction Management